2012
DOI: 10.1371/journal.pone.0046013
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Connectivity of Trypanosoma cruzi Reservoirs and Triatoma pallidipennis Hosts in an Anthropogenic Landscape with Endemic Chagas Disease

Abstract: Traditional methods for Chagas disease prevention are targeted at domestic vector reduction, as well as control of transfusion and maternal-fetal transmission. Population connectivity of Trypanosoma cruzi-infected vectors and hosts, among sylvatic, ecotone and domestic habitats could jeopardize targeted efforts to reduce human exposure. This connectivity was evaluated in a Mexican community with reports of high vector infestation, human infection, and Chagas disease, surrounded by agricultural and natural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 46 publications
3
50
0
2
Order By: Relevance
“…Seven species of rodent were collected, all of which had individuals that were infected. Ramsey et al (2012) found an ecological connectivity between sylvatic areas, ecotone between sylvatic and domestic areas, and domestic habitats that provided for reservoir species dispersal. They point out that in the modern world, human expansion of domestic environments into sylvatic cycles results in chronic Chagas disease infection.…”
Section: Burned Rock Middens and Triatomine Insectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Seven species of rodent were collected, all of which had individuals that were infected. Ramsey et al (2012) found an ecological connectivity between sylvatic areas, ecotone between sylvatic and domestic areas, and domestic habitats that provided for reservoir species dispersal. They point out that in the modern world, human expansion of domestic environments into sylvatic cycles results in chronic Chagas disease infection.…”
Section: Burned Rock Middens and Triatomine Insectsmentioning
confidence: 93%
“…The analysis of anthropogenic landscape change related to Chagas disease by Ramsey et al (2012) presents a modern example of ecological connectivity of Chagas disease with human development of the environment. These researchers addressed the basic question of how triatomines become reestablished in a Mexican village rapidly after a successful triatomine extermination program.…”
Section: Burned Rock Middens and Triatomine Insectsmentioning
confidence: 99%
“…Recent studies on the ecological connectivity of vector and parasite host communities within anthropogenic landscapes are providing novel insights into the spatial epidemiology linked to T. cruzi transmission, vector population dynamics, and mammal host metacommunities (Ramsey et al, 2012;Gottdenker et al, 2014;Fernandez et al, 2014). Metacommunities resulting from habitat filtering in anthropogenic landscapes influence bloodmeal use by triatomines, and generally increase T. cruzi prevalence (Gottdenker et al, 2012;Ramsey et al, 2012;Gurtler et al, 2014). Furthermore, regional-scale phylogeographic studies of T. cruzi highlight the influence of sylvatic habitats surrounding human-transformed land as sources of parasite diversity (Ocana-Mayorga et al, 2010;Lima et al, 2014a).…”
Section: Trypanosoma Cruzi Transmission Is Clearly Zoonotic and Anthrmentioning
confidence: 99%
“…Thebloodmeal source of all T. dimidiata was identified using PCR as previously described (Mota et al, 2007;Ramsey et al,2012). The proportion of bugs containing human blood was used to calculate the adjusted prevalence of single or mixed human bloodmeals in each habitat.…”
Section: Triatominesmentioning
confidence: 99%
See 1 more Smart Citation